Propaganda in Art; Home as a Metaphor - Gür, Nazif (Fırat University, 2024)
House, which is the space where the sociological, economic, ideological, physiological and aesthetic shelter needs of human beings are met, is also a metaphor that attributes dynamic meanings such as family, home and shelter. In this sense, home is a place that needs to be defended. During World War I, aware that the house was a place that needed to be defended, propagandists often used the house as a metaphor for the country in posters. Home metaphors in propaganda posters designed to encourage participation in the army in the period when there was no compulsory military service policy triggered both basic human emotions and the subject looking at the poster was directed to make a moral choice. This choice plays a manipulative role between protecting your home from enemies or not, and therefore between protecting your country and not protecting it. Thus, feelings of patriotism were created in society through the metaphor of home, which has collective meanings. The aim of the study is to make a descriptive analysis of the purpose and meaning of the posters, which were home metaphors, during World War I. As a result of the study, it was seen that the house turned into a political metaphor in art as a propaganda tool for recruiting soldiers and purchasing bonds. It is hoped that the article will contribute to the literature in terms of proposing a new perspective on both the propaganda posters used in World War I and the home metaphor in art.

İnsanoğlunun sosyolojik, ekonomik, ideolojik, fizyolojik ve estetik barınma ihtiyaçlarının karşılandığı uzamlar olan ev aynı zamanda aile, yuva ve sığınak gibi dinamik anlamlar atfeden bir metafordur. Bu anlamlarıyla ev, savunulması gereken bir yerdir. I. Dünya Savaşı sırasında evin savunulması gereken bir yer olduğunun bilinciyle propagandacılar evi ülkenin metaforu olarak posterlerde sıklıkla kullanmışlardır. Zorunlu askerlik politikasının olmadığı dönemde orduya katılımı teşvik etmek için tasarlanan propaganda posterlerindeki ev metaforları hem temel insani duygularını tetiklemiş hem de postere bakan özne ahlaki bir seçim yapmaya yöneltilmiştir. Bu seçim, evini düşmanlardan korumak ile korumamak arasında dolayısıyla da ülkesini korumak ile korumamak arasında manipülatif rol oynamaktadır. Böylece kolektif anlamlara sahip olan ev metaforu aracılığıyla toplumda vatanseverlik duyguları örülmüştür. Çalışmanın amacı I. Dünya savaşında ev metaforu olan posterlerin hangi amaç doğrultusunda, hangi anlamlarda kullanıldığının betimsel analizini yapmaktır. Çalışma sonucunda evin, asker toplama ve tahvil satın alınması için propaganda aracı olarak sanatta siyasi bir metafora dönüştüğü görülmüştür. Makale hem I. Dünya Savaşı’ında kullanılan propaganda posterlerine hem de sanatta ev metaforuna yönelik yeni bir bakıs? ac?ısı önermesi açısından literature katkı sağlayacağı ümit edilmektedir.
SANATTA PROPAGANDA; POSTERDE BİR METAFOR OLARAK EV
Keywords: Computing Applications in Arts and Humanities; Sanat ve Beşeri Bilimlerde Bilgi İşleme